Apple, Inc. : transparency in corporate statements about the CEO - Kim, Paul; Lee, Jon; Lee, Steve; O'Rourke, James S., 1946- (London : SAGE Publications Ltd, 2017)
On January 14, 2009, Steve Jobs, CEO of Apple Inc., announced he was taking a six-month medical leave of absence just nine days after he reassured the public that he would be continuing as CEO. The media and public feel misled and investors are wary of Apple's post-Jobs future. The issue for Apple is whether investors and the public are entitled to more information and, if so, how much?
Originally published in Kim, P., Lee, J., Lee, S., & ORourke, J. S. (2009). Apple, Inc.: Transparency in corporate statements about the CEO. 09-04. Notre Dame, IN: The Eugene D. Fanning Center for Business Communication, Mendoza College of Business, University of Notre Dame.
Description based on XML content.
Keywords: elektronické knihy; Apple Computer, Inc; electronic books; Corporations -- Public relations; Corporations -- Investor relations